AN INITIAL EXPLORATION ON TERRORISM ISSUES IN MALAYSIA AND INDONESIA: THE CASE OF THE WALL STREET JOURNAL - Fauziah Hassan; Sofia Hayati Yusoﬀ; Siti Zobidah Omar (Informasi, 2018)
The symbiotic relationship between Islam and media is inevitable. The frequent of media coverage about Islam has been researched by many especially since the remarkable incident of September 11 in 2001. From that moment, Islam has been viewed and labelled as negative by the Western media specifically to the Muslims living in America and those in the Middle East countries. This phenomenon has been contagious to the Muslims in Southeast Asian countries such as Malaysia and Indonesia as these two countries are believed to have a connection with recent terrorist groups such as Islamic State of Iraq and the Levant (ISIL) and Islamic State in Iraq and Syria (ISIS). Therefore, this study was conducted to see the frequent coverage specifically on terrorism issues as reported by the Wall Street Journal (WSJ) and to explore the news themes that emerged in the news reporting. To realize this study, the researchers applied both quantitative and qualitative analysis to analyse the online news articles found in WSJ from year 2012 until 2013. The qualitative software was used in this study namely QSR Nvivo 11 to help and assist the researchers to store, manage and codify the news and also the quantitative software which is SPSS to calculate the frequencies of the reporting. The findings revealed that WSJ reported news related to terrorism in Malaysia and Indonesia frequently but it seems that Indonesia received higher percentage compared to Malaysia. In terms of news themes, the results found four major themes that are very much related to terrorism issues such as terrorist attacks, suspected as terrorist and robbery from both issues happened in Malaysia and Indonesia.